(3TQM aUhd CHbQGWs - (3CHh GdbGSe YHO GdQMef Hf Ydj Hf CHi UGObs; (3GHbQGW GdMcjes
(3ChdgG (B:s
(3CeG HYO MeO Gddg HLejY eMGeOg , hGdKfGA Ydjg gh Cgdg , hGdUdGI Ydi QShdg eMeO GdfHi hBdg hSde hbO cGf ef GdeJbOejf hGdeJCNQjf eef JcdehG ai GdWH QChG Cf jOhfhG HYOge LedG hLhGeY ef GUhdg s
(3BNQgG (B:s
(3hCeG GdaVhd GdeOdSI hGdJi bO CYjO PcQgG HCNQI ef GdcJGH , abO JQcfG PcQgG TabI Ydi ahJ GdReGf HeGdG jLOi faYkG , hGddg JYGdi hdi GdNjQ hGdNjQI s
(3fSNI QGHYIs
(3hgj ai SHY ebGdGJs
(3hbO aUd GdjYbhHi JGQjNg (B1:107-115 (3Gdbhd ai gPG GdcJGHs
(3hacQ Cfg eQJH Ydi SHYI hNeSjf HGHkG gi GdJi JSei GdJYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdWHs